Ion channel molecular complexes in vascular smooth muscle - Pereira da Silva, Eric A.; Martín-Aragón Baudel, Miguel; Navedo, Manuel F.; Nieves-Cintrón, Madeline (Frontiers in Physiology, 2022)
Vascular smooth muscle excitability is controlled by ion channels that influence membrane potential and intracellular calcium concentration. Voltage-dependent L-type CaV1.2 channels, transient receptor potential channels, Voltage (KV), and Ca2+-activated K+ (BK) channels are key regulators of vascular smooth muscle excitability and contractility. These channels are regulated by various signaling cues, including protein kinases and phosphatases. The effects of these ubiquitous signaling molecules often depend on the formation of macromolecular complexes that provide a platform for targeting and compartmentalizing signaling events to specific substrates. In this manuscript, we summarize our current understanding of specific molecular complexes involving CaV1.2, TRP, and KV and BK channels and their contribution to regulating vascular physiology.